MITOCHONDRIAL DNA VARIATION AMONG ISOLATED AMPHIBIAN POPULATIONS - Krishnappa S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Mitochondrial DNA (mtDNA) variation plays a critical role in understanding the genetic structure, evolutionary processes, and ecological adaptations of isolated amphibian populations. Amphibians, characterized by their reliance on specific environmental conditions, are often subject to geographical and ecological isolation, which leads to the differentiation of genetic traits, including mitochondrial markers. This study explores the patterns of mtDNA variation among amphibian populations that have become isolated due to both natural events, such as climatic changes during glaciations, and human-induced fragmentation of habitats. Mitochondrial DNA is particularly useful in population genetics studies because of its maternal inheritance, rapid mutation rate, and the absence of recombination, making it an effective tool for tracing population histories and assessing genetic connectivity. Isolated amphibian populations, particularly those in fragmented habitats or refugia, often exhibit distinct mitochondrial haplotypes, reflecting long-term genetic divergence. The degree of variation among these populations provides insights into the mechanisms of evolutionary differentiation, such as genetic drift, natural selection, and historical climate events. Additionally, the impact of anthropogenic changes, such as habitat destruction and climate change, has amplified isolation and reduced gene flow, leading to further genetic differentiation and potential inbreeding risks. Through mtDNA analysis, researchers can track evolutionary processes such as sympatric divergence and hybridization events, where introgression of mitochondrial haplotypes may occur. These findings highlight the importance of mitochondrial DNA as a tool for understanding evolutionary dynamics, informing conservation strategies, and preserving genetic diversity in amphibians. Ultimately, the study of mtDNA variation in isolated amphibian populations is crucial for assessing the long-term survival of these species, as they face ongoing environmental pressures.